Parents' knowledge, attitudes and beliefs regarding sun protection in children: a qualitative study - Zoe Littlewood; Sheila Greenfield (BMC, 2018)
Abstract Background Childhood is a critical period for sun protection, when the skin is particularly susceptible to the carcinogenic effects of ultraviolet radiation. Children are dependent upon parents to implement sun protective measures. Existing qualitative research exploring parents' attitudes and beliefs underpinning children's sun protection is from Australia, which has the highest melanoma incidence rates globally, and thus benefits from widespread sun protection awareness campaigns. Parents' sun protective behaviour may, therefore, differ between Australia and the UK. This study investigates the topic in a UK context, using qualitative methodology to gain detailed insights into a relatively under-researched area. The aim of the study was to explore parents' knowledge and understanding of sun protection in children, and factors that motivate and challenge them in this area. Finally, it aimed to determine if and how ethnicity and skin type influence these attitudes and beliefs. Methods Twenty-two semi-structured individual interviews were carried out with parents of children aged 5 years or younger, recruited from local nurseries. Transcripts were analysed using thematic analysis. Results Four overarching themes emerged, each incorporating two to three sub-themes. 'Attitudes towards children's sun protection' refers to the fact that parents considered sun protection to be important for children, a finding which was consistent between different skin types. 'Sun protection practices' brings together several protective behaviours adopted in children and, to a lesser degree, in parents, and their associated disadvantages. 'Sun safety knowledge' refers to parents' awareness of the risks of sun exposure and the need for protection, and illustrates where gaps in knowledge exist, such as regarding the need for vitamin D, and the importance of vigilant sun protection even in the UK. Finally, 'motivating and facilitating factors' highlights motivations for sun protection in children, and factors that facilitate it in practice. Conclusion This study found parents to be motivated and concerned about children's sun protection, irrespective of children's ethnicity, and aware of appropriate protective behaviours. It indicates key challenges which could be targeted in future campaigns in order to improve sun protection in children and reduce uncertainty and anxiety regarding sun safety amongst parents.